Antecedents of Employee Turnover Intention on Food and Beverage - Tria Aminun Ariani; Anwar Mansyur (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the influence of Affective Commitment, Normative Commitment, and Occupational Stress on Turnover Intention. The research method used is a quantitative research method with a questionnaire as the data collection tool. The sampling technique used was purposive sampling, with a sample size of 115 employees of Coffeeshop Food & Beverage in the West Region of Semarang City. Data analysis was conducted using validity and reliability tests and multiple linear regression. The results of this analysis indicate that there is a positive insignificant influence of affective commitment on turnover intention, a negative insignificant influence of normative commitment on turnover intention and a positive significant influence of occupational stress on turnover intention. Simultaneously, all three independent variables significantly influence turnover intention. This finding indicates that job stress will influence high turnover intention, and the negative influence of normative commitment will have an impact on no intention to leave low. This study provides theoretical implications in the development of human resources management concepts and suggests that organizations always pay attention to employees to prevent higher turnover intentions, with policies that are more beneficial to employees.